2011
DOI: 10.1007/s10661-011-2273-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the breeding habitats for two endangered raptor species along the Sava River basin, Croatia

Abstract: Changes in habitat suitable for breeding of two sympatric raptor species (Haliaeetus albicilla and Aquila pomarina) were analysed along one of the most important breeding sites in Croatia for both species. The habitat suitability modelling was used to assess the influence of forestry practice during 2000-2006 using the known data on nesting places along research area. The four most important variables for lesser spotted eagle were elevation, distance from the nearest pasture, vertical distance to the nearest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…With a few notable exceptions, little detailed information currently exists on habitat selection of white‐tailed eagles in coastal areas in Norway (Willgohs 1961, Nygård et al 2010). Generally, white‐tailed eagle habitat is usually connected to coastal areas, lakes, rivers, and wetlands (Radovic and Mikuska 2009, Nygård et al 2010, van Rijn et al 2010, Radovic and Jelaska 2012). Studies elsewhere have shown that white‐tailed eagles may avoid human activity (Lõhmus 2001, Radovic and Mikuska 2009).…”
mentioning
confidence: 99%
“…With a few notable exceptions, little detailed information currently exists on habitat selection of white‐tailed eagles in coastal areas in Norway (Willgohs 1961, Nygård et al 2010). Generally, white‐tailed eagle habitat is usually connected to coastal areas, lakes, rivers, and wetlands (Radovic and Mikuska 2009, Nygård et al 2010, van Rijn et al 2010, Radovic and Jelaska 2012). Studies elsewhere have shown that white‐tailed eagles may avoid human activity (Lõhmus 2001, Radovic and Mikuska 2009).…”
mentioning
confidence: 99%